Combating inequalities: What role for universal social protection? - Shahrashoub Razavi; Umberto Cattaneo; Helmut Schwarzer; Andrea Visentin (International Labour Organization (ILO), 2024)
The primary aim of this study is to provide evidence regarding the impact of social protection benefits, taxes and social security contributions in reducing income inequalities. The study employs a well-established methodology to estimate the partial redistributive effect of contributory and non-contributory pensions, family benefits, unemployment benefits, sickness and employment injury benefits, disability benefits, social security contributions, as well as income and property taxes. The partial redistributive effect corresponds to the percentage decrease in the Gini coefficient that is attributable to each social protection benefit and tax. The main data input is microdata from the Luxembourg Income Study (LIS). The evidence presented shows that social protection benefits, and its financing through taxes and social security contributions, are effective policy measures for reducing income inequalities. On average countries that spend more on social protection are those that experience larger reductions in income inequality. The paper concludes with practical recommendations on how to finance and design social protection systems that reduce inequalities, as well as ideas for future research in this area.
Keywords: 330